Agricultural engineering standards in slaughtering operation - Aranguren, Darwin C.; Suministrado, Delfin C.; Eusebio, Romulo E.
The availability of a comprehensive Philippine Agricultural Engineering Standards is required to ensure the quality agricultural engineering technologies, systems and services in terms of design, construction, operation and safety. Over the past years, several projects on development of agricultural engineering standards funded by various agencies of the Department of Agriculture were conducted and one hundred twenty (120) agricultural engineering standards on production machinery, postharvest machinery, engineering materials and agricultural structures were formulated, reviewed, presented and adopted. Recently, standard specifications and methods of tests for equipment used in slaughtering hogs and large ruminants were formulated. For slaughtering equipment, the standards were formulated to answer the need of ensuring the optimal handling of animals while at the same time complies with humane slaughtering procedures.
Keywords: Slaughtering equipment; Hog restrainer; Hog electric stunner; Hog scalder; Dehairing machine; Splitting saw; Overhead rail system; Stunning box/knocking pen; Captive bolt; Dehider; Platform